China's Anti‐dumping Problems and Mitigation through Regional Trade Agreements. (November 2016) - Sun, Yanlin; Whalley, John
Abstract: The present paper explores the opportunities for China's regional trade agreement (RTA) initiatives to mitigate its anti‐dumping problems. The paper highlights the severity and discriminatory nature of China's anti‐dumping problems. The high concentration of the share of anti‐dumping actions taken by the top 4 and top 8 anti‐dumping initiators is noted. Our finding of a weak effect of existing RTAs on mitigating China's anti‐dumping problems supports the argument that China could become more active in mitigating anti‐dumping problems through RTA negotiations. An RTA can include a higher level of openness in exchange for an improvement in regional anti‐dumping provisions. Case studies on RTAs involving the EU, the USA and India offer some precedents for offering inducements and modifying regional anti‐dumping provisions. The approaches for China may lie in obtaining market economy status from intensive anti‐dumping initiators at RTA levels and also altering regional anti‐dumping provisions that could be put in place in exchange for some potential concessions.